Comparing High and Low-Dose Radio-Iodine Therapy in Thyroid Remnant Ablation Among Intermediate and Low-Risk Papillary Thyroid Carcinoma Patients-Single Centre Experience - Tahira Yasmin; Sadia Adnan; Muhammad Numair Younis; Arzoo Fatima; Abubaker Shahid (SAGE Publishing, 2021)
The role of Iodine-131 therapy is well established as an adjuvant therapy and for thyroid remnant ablation in differentiated thyroid cancer (DTC); however controversy still exists regarding its appropriate dose. Purpose of this study was to compare the effectiveness of low-dose and high-dose Iodine-131 ablation therapies in low- and intermediate-risk PTC patients. Eighty-four patients were divided equally into Group I: Ablated with high dose of Iodine-131 and Group II: Ablated with low dose of Iodine-131. Iodine-131 WBS, serum TG levels and USG neck of all patients were performed at first presentation, 6 months, 1 year, and 2 years follow up. Results are as follows: Group I: 64%, 72%, and 76% intermediate-risk patients were disease free at the follow up intervals of 6 months, 1 year, and 2 years, respectively. Similarly 70%, 82%, and 82% low-risk patients were disease free at above mentioned intervals. Group II: 56%, 60%, and 64% were disease free among intermediate-risk patients while percentage of disease free low-risk patients was 70%, 76%, and 76% at follow up intervals. Low dose of radioactive Iodine-131 was found as effective as high dose in thyroid remnant ablation of PTC patients.